Evaluation of biosafety knowledge among professionals at the material and sterilization center of a reference Hospital - Teixeira Lobo, Letícia; Nelson Rolim Remigio, Gabriel; Henrique Andrade Galvão, Bruno (Disciplinarum Scientia | Saúde, 2024)
Objective: to assess the knowledge and perception of biosafety among Central Sterile Supply Department (CSSD) professionals at a reference university hospital in Paraíba in 2022. Methods: descriptive observational study. The study population was formed by health professionals working in the CSSD at the hospital studied. The sample consisted of professionals who agreed to take part in the study and sign the informed consent form. The data was analyzed descriptively. Results: a total of 42 CSSD employees were interviewed. Of those interviewed, 52.4% had already taken a course on biosafety. Only 59.5% of the participants said they were aware of biosafety legislation in Brazil. Furthermore, around 80% of the professionals rated their knowledge and application of biosafety standards as at least satisfactory. Conclusion: CSSD professionals have satisfactory knowledge of biosafety standards, but there is still a need for greater educational investment in this area.